A qualitative assessment of the effectiveness of a group diabetic education programme using motivational interviewing in underserved communities in South Africa. - Botes, Anna Susanna (Stellenbosch : University of Stellenbosch, 2015)
Thesis (MFamMed) --Stellenbosch University, 2011